Integrating target costing (TC) indicators within the balanced scorecard (BSC) model: an empirical evidence of selected Asian companies / Suzana Sulaiman …[et al.] - Sulaiman, Suzana; Omar, Normah; Abdul Rahman, Ibrahim Kamal; Ueno, Susumo; Jimmy, Tsay
Target Costing (TC) is not only seen to be related to cost reduction. Instead, quality and functionality features, in similar extent, should be seriously perceived when determining of marketplace and customers' attitudes in the planning and design stages of products. This particularly requires serious and effective integration of relative TC indicators to establish future customers' expectations toward company's products. This project aims to examine the integration of TC indicators within the Balanced Scorecard (BSC) model in three selected Asian countries; Japan, Thailand and Malaysia with a considerable focus on Malaysia. The integration framework developed posits that the four TC's principles of "Price-led", "Customer-focused", "Design-centered", and "Crossfunctional" can be reflected in the four BSC's perspectives of "Financial", "Customer", "Internal Process", and "Learning and Growth". The findings indicate that the proposed framework strikes to get the right balance across the crucial elements of TC which include cost reduction, quality, functionality, and lead time.